Effects of Eryngii mushroom (Pleurotus eryngii) and Lactobacillus plantarum on growth performance, immunity and disease resistance of Pangasius catfish (Pangasius bocourti, Sauvage 1880) - Van Doan H. (2017)
Â© 2016, Springer Science+Business Media Dordrecht. This study was conducted to evaluate the effects of Eryngii mushroom, Pleurotus eryngii (PE), and Lactobacillus plantarum single or combined on growth, innate immune response and disease resistance of the Pangasius catfish, Pangasius bocourti. Two hundred forty fish were divided into four treatments, i.e., 0Â gÂ kg −1 PE (Control, Diet 1), 3Â gÂ kg −1 PE (Diet 2), 10 8 Â cfuÂ g −1 L.plantarum (Diet 3) and 3Â gÂ kg −1 PEÂ +Â 10 8 Â cfuÂ g −1 L. plantarum (Diet 4). Fish were culture in glass tanks with water volume approximately of 150Â l, and each treatment had four replications with 15 fish per replication. Following 30, 60 and 90Â days of the feeding trial, specific growth rate (SGR), feed conversion ratio (FCR), serum lysozyme, phagocytosis and respiratory burst activities were measured. SGR and FCR were significantly improved in fish fed supplemented diets after 90Â days of the feeding trial. Serum lysozyme, phagocytosis and respiratory burst activity of fish were significantly stimulated by both PE and L. plantarum diets; however, the highest innate immune response was observed in fish fed synbiotic diet. At the end of the experiment, five fish were randomly selected for a challenge test against Aeromonas hydrophila. The post-challenge survival rate of the fish fed supplemented diets was significantly greater than the control treatment, and the highest post-challenge survival rate was observed in synbiotic diet. The results revealed that dietary supplementation of PE and L. plantarum stimulated growth, immunity and disease resistance of the P. bocourti.